Non-Knowledge and Digital Cultures - Bernard, Andreas; Koch, Matthias; Leeker, Martina (Digital Cultures, 2018)
Making available massive amounts of data that are generated, distributed, and modeled, digital media provide us with the possibility of abundant information and knowledge. This possibility has been attracting various scenarios in which technology either eliminates non-knowledge or plants it deep within contemporary cultures through the universal power and opacity of algorithms. This volume comprises contributions from media studies, literary studies, sociology, ethnography, anthropology, and philosophy to discuss non-knowledge as an important concept for understanding contemporary digital cultures.